The Fellowship of Orthodox Youth as an element in the activation of the orthodox laity = Bractwo Młodzieży Prawosławnej jako element aktywizacji prawosławnego laikatu - Dudra, Stefan (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Orthodox fellowships, with their centuries-old tradition were the main centers of Orthodox cultural life. They were involved in charitable, welfare and educational activities, financed the establishment of hospitals and shelters, and organized secular and religious celebrations. Through their publishing activities, they shaped the awareness of the faithful. During the period of the Polish People`s Republic, their activities were very limited for political reasons.
Keywords: Orthodoxy; laity; Fellowship of Orthodox Youth; prawosławie; laikat; Bractwo Młodzieży Prawosławnej